EPICOH 2.0.13: Improving the Impact, Utrecht, The Netherlands 18-23 June 2013 - Redazione, La (La Medicina del Lavoro, 2012)
EPICOH 2.0.13: Improving the Impact, Utrecht, The Netherlands 18-23 June 2013